TINJAUAN YURIDIS TERHADAP PEMBUKTIAN HARTA BERSAMA DALAM PUTUSAN NOMOR 0133/Pdt.G/2016/PA.Kdr - Nirvana Rifka Dian Kumala; Mahfud Fahrazi (MIZAN, Jurnal Ilmu Hukum, 2023)
This master thesis is about the joint property’s evidence of the verdict number 0133/Pdt.G/2016/PA.Kdr. The evidences that submitted by defendant counterclaim were an authentic deed and two witnesses who are siblings of the defendant counterclaim, so according to that the judges decided to share the joint property of marriage againts the Compilation of Islam Law Section 97. The purposes of this master thesis are to analyze the validity of the evidences in joint property’s evidence and to analyze the judge’s considerations of the verdict number 0133/Pdt.G/2016/PA.Kdr. This master thesis is a normative research. This master thesis concludes that the validity of the evidences in joint property’s evidence of the verdrict number 0133/Pdt.G/2016/PA.Kdr according to Section 145 of HIR, Section 172 of RBg and Section 1910 of Indonesian Civil Code, plaintiff counterclaim submitted an authentic deed and two witnesses as evidences so both of them were valid as evidences. And then the evidences that submited by defendant counterclaim were an authentic deed and two witnesses who are the siblings of defendant counterclaim, so that the two witnesses that submitted by defendant counterclaim does not fulfill the formal requirement of evidence based on the codes. The verdict does not fulfill the elements of legal certainty.